Why do the arms extract less oxygen than the legs during exercise? - Calbet, J. A. L.; Holmberg, H. C.; Rosdahl, H.; van Hall, G.; Jensen-Urstad, M.; Saltin, B. (American Journal of Physiology - Regulatory, Integrative and Comparative Physiology, 2005)
To determine if the conditions for O2 utilization and O2 off-loading from the hemoglobin molecule are different in exercising arms and legs six cross-country skiers with a maximal oxygen uptake (VO2max) of 5.1 ± 0.3 l min-1 (mean ± SD) participated in the study. Femoral and subclavian vein blood flow, blood gases and acid base balance were determined during skiing on a treadmill at ~76% of VO2max and at VO2max with different techniques: the diagonal stride (combined arm and leg exercise), the double poling (predominantly arm exercise) and leg skiing (predominantly leg exercise). During submaximal exercise, regardless of the exercise mode, the percentage of O2 extraction was always higher for the legs (range of mean values: 83-90%) than for the arms, even during double poling (range of individual values: 62-81%). At maximal exercise (diagonal) the corresponding mean values were 93 and 85% , (n=3; P < 0.05). During exercise, mean arm O2 extraction correlated with the P50 (r=0.93, P < 0.05), but for a given value of P50 O2 extraction was always higher in the legs than in the arms. The mean capillary muscle O2 conductance of the arm during double poling was 14.5 ± 2.6 ml min-1 mmHg-1 and the mean capillary PO2 47.7 ± 2.6 mmHg. The corresponding values for the legs during maximal exercise with the diagonal technique were 48.3 ± 13.0 ml min-1 mmHg-1 and 33.8 ± 2.6 mmHg, respectively. Since the conditions for the O2 off-loading from the hemoglobin are similar in leg and arm muscles, the observed differences in maximal arm and leg O2 extraction should be attributed to other factors, such as a higher heterogeneity in the distribution of blood flow between muscles, or functional portions of the same muscle, shorter mean transit time, smaller diffusing area, and larger diffusing distance, in arms than in legs.